2023
DOI: 10.1039/d3cc02151c
|View full text |Cite
|
Sign up to set email alerts
|

B(C6F5)3-catalyzed regio- and stereoselective thiosulfonylation of terminal alkynes with thiosulfonates

Abstract: Herein, a metal-free main-group catalysis system for thiosulfonylation of terminal alkynes with thiosulfonates has been eatablished by using commercial available B(C6F5)3 as catalyst. The protocol provides a highly regio- and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…These existing approaches are restricted to the addition of aryl sulfones, the presynthesis of enamide substrates, and multistep reactions. Nowadays, intermolecular regioselective 1,2-difunctionalization of alkynes is a potent tool for upgrading feedstocks into molecules because it permits the simultaneous installation of two vicinal new bonds. Several approaches including hydrosulfonylation, aminosulfonylation, carbosulfonylation, oxysulfonylation, thiosulfonylation, seleno-sulfonylation, and halosulfonylation have been developed for the synthesis of these sulfonylated compounds. In 2017, Bi et al reported an intermolecular radical reaction using silver catalyst for the synthesis of aminosulfonylation of alkynes (Scheme b) .…”
Section: Introductionmentioning
confidence: 99%
“…These existing approaches are restricted to the addition of aryl sulfones, the presynthesis of enamide substrates, and multistep reactions. Nowadays, intermolecular regioselective 1,2-difunctionalization of alkynes is a potent tool for upgrading feedstocks into molecules because it permits the simultaneous installation of two vicinal new bonds. Several approaches including hydrosulfonylation, aminosulfonylation, carbosulfonylation, oxysulfonylation, thiosulfonylation, seleno-sulfonylation, and halosulfonylation have been developed for the synthesis of these sulfonylated compounds. In 2017, Bi et al reported an intermolecular radical reaction using silver catalyst for the synthesis of aminosulfonylation of alkynes (Scheme b) .…”
Section: Introductionmentioning
confidence: 99%